Implementation Utilization of Zakat Funds Inhabitant Muhammadiyah Baubau City during the Covid-19 Period In accordance Guidelines for Amil Zakat Infaq Alms Muhammadiyah (Lazismu) - Sujana, I Wayan; Ridzal, Nining Asniar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Implementation of the Utilization of Zakat Funds for Muhammadiyah Citizens in the Covid-19 Era has not been in accordance with the Guidelines for the Amil Zakat Ifaq Alms Muhammadiya Institute (LAZISMU) of the Muhammadiyah Central Leadership. Zakat is an implementation of excess property that is entrusted to the rich, which must be issued to poor people as an implementation of devotion and elevates the underprivileged people so that there is no economic inequality between Muslims. Conducting interviews and observations on the management of zakat of Muhammadiyah residents of Baubau city during the Covid-19 pandemic, found that zakat payments were made by Muhammadiyah residents by channeling their zakat directly to poor mustahik, zakat distribution has not fulfilled the necessities of life for mustahik in one year, the collection of zakat funds is still in nature. wait, there is no data on the potential of Muzaki and mustahik members of Muhammadiyah, this is not in accordance with the implementation of zakat management by the amil zakat institution infaq shadakah Muhammadiyah (LAZISMU). However, because of the understanding of the understanding in the implementation of zakat infaq management, Muhammadiyah members are shadakah so there needs to be a variety of approaches and strategic policies that are more used so that they can be used and the distribution and accountability of zakat management is in accordance with the guidelines for collecting and compiling zakat, infaq and shadakah.